Leadership the critical difference - Tracy, Brian (Chicago : Nightingale-Conant Corporation.)
How to become a better leader. The importance of vision and determining your mission. The need for action orientation. Courage, the vital factor. Strategy and tactics. Inspiring others and gaining followers. The transformational leader. Self-esteem. Listening. Integrity. .
Keywords: Executive ability; Leadership; Management